2010
DOI: 10.1007/s10484-010-9133-y
|View full text |Cite
|
Sign up to set email alerts
|

Biofeedback of Heart Rate Variability and Related Physiology: A Critical Review

Abstract: Low heart rate variability (HRV) characterizes several medical and psychological diseases. HRV biofeedback is a newly developed approach that may have some use for treating the array of disorders in which HRV is relatively low. This review critically appraises evidence for the effectiveness of HRV and related biofeedback across 14 studies in improving (1) HRV and baroreflex outcomes and (2) clinical outcomes. Results revealed that HRV biofeedback consistently effectuates acute improvements during biofeedback p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
142
0
9

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(159 citation statements)
references
References 38 publications
8
142
0
9
Order By: Relevance
“…A HR that is variable and responsive to demands is believed to bestow a survival advantage, whereas reduced HRV may be associated with poorer CV health and outcomes (Nunan et al, 2010;Routledge et al, 2010;Thayer et al, 2010;Wheat & Larkin, 2010).…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…A HR that is variable and responsive to demands is believed to bestow a survival advantage, whereas reduced HRV may be associated with poorer CV health and outcomes (Nunan et al, 2010;Routledge et al, 2010;Thayer et al, 2010;Wheat & Larkin, 2010).…”
Section: Heart Rate Variabilitymentioning
confidence: 99%
“…It has been suggested that resonance frequency breathing (i.e., the breathing frequency that causes the largest HR oscillation amplitude) may strengthen baroreflexes, thus improving the autonomic functioning (Vaschillo et al 2002;Lehrer et al 2003). HRV BF has shown to be useful in treating symptoms in various disorders characterized by aberration of the ANS (Wheat and Larkin 2010), including posttraumatic stress disorder (PTSD) (Zucker et al 2009), depression (Siepmann et al 2008) and heart disease (Nolan et al 2005) as well as musculoskeletal pain (Hasset et al 2007;Kapitza et al 2010). However, further controlled studies are needed on muscle pain.…”
Section: Introductionmentioning
confidence: 99%
“…When both emotion regulation problems are present and HRV is low, intervention programs may be considered which have been shown to be beneficial in people without intellectual disabilities, e.g. HRV-biofeedback (Wheat and Larkin 2010). Such interventions may boost emotion regulation abilities and, thus, may indirectly enhance quality of life in people with intellectual disabilities.…”
Section: Discussionmentioning
confidence: 99%